Contemporary economic issues - Chamberlain, Neil W. (Homewood, Illinois: R. D. Irwin, 1973)
Both the citizen on the street and the professional economist in his study often refer to "the economic system." Neither very often takes the time to examine what he means by that term. With only a little reflection, agreement could probably be reached on a definition that would read something like: "a national unit whose component parts are so functionally related to each other as collectively to realize certain desired economic results."
1. The Economic Base of Urban Problems -- 2. Poverty in an Affluent Society -- 3. Economic Issues in Health Services -- 4. The Economics of Education: A Survey -- 5. Current Issues in Transportation -- 6. Population.
Includes bibliographical references.
Keywords: UNITED STATES -- ECONOMIC POLICY